Application of cell free DNA in ART. (24th March 2022) - Alizadegan, Amin; Dianat-Moghadam, Hassan; Shadman, Nasrin; Nouri, Mohammad; Hamdi, Kobra; Ghasemzadeh, Alieh; Akbarzadeh, Maryam; Sarvarian, Parisa; Mehdizadeh, Amir; Dolati, Sanam; Yousefi, Mehdi
Abstract: Various biopsy and sampling methods are used for preimplantation genetic diagnosis (PGD) of embryo. This method benefits blastomer/trophectoderm biopsy to improve the clinical outcome of in vitro fertilization (IVF). However, all of these procedures are invasive and have adverse effects on embryo development. Additionally, these procedures require expensive equipment and well-experienced technicians. Regarding these limitations, designing non-invasive methods is necessary. One of the recently proposed non-invasive and applicable methods is cell free DNA (cfDNA) molecule evaluation that have opened up exciting opportunities in the molecular diagnosis of embryo and fetus chromosomal aneuploidy. cfDNA is present in body fluids; especially blood, follicular fluid, amniotic fluid, spent embryo culture medium (SCM) and blastocoel fluid. Overall, this review highlights the cfDNA biomarker might constitute a supplemental tool for improving IVF and pregnancy outcomes, female infertility management. However, the successful application of cfDNA demands an understanding of its biological properties, kinetics, time of collection, high sensitivity and specificity cfDNA detection methods, and their limitation and challenges in the clinical settings. In this review we also describe ethical aspects of cfDNA testing. Highlights: cfDNA is a short fragment of dsDNA released from cells undergoing cell death or dividing. Discovery of cfDNA in SCM is a source of embryonic DNA for valuation of embryo quality. cfDNA can facilitate appropriate parental counseling in the future.